2009
DOI: 10.1021/la901938e
|View full text |Cite
|
Sign up to set email alerts
|

Patterning Discrete Stem Cell Culture Environments via Localized Self-Assembled Monolayer Replacement

Abstract: Self-assembled monolayers (SAMs) of alkanethiolates on gold have become an important tool for probing cell-material interactions. Emerging studies in stem cell biology are particularly reliant on well-defined model substrates, and rapid and highly controllable fabrication methods may be necessary to characterize the wide array of stem cell-material interactions. Therefore, this study describes a rapid method to create SAM cell culture substrates with multiple discrete regions of controlled peptide identity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 46 publications
6
55
0
Order By: Relevance
“…Alternatively, a self-assembled monolayer ͑SAM͒ substrate was developed to create arrays of spatially distinct hMSC culture environments. 147 A broad range of cell adhesion peptide densities of hMSCs adhered to patterned features was observed. Moreover, the peptide density significantly affects the formation, extension, and focusing the hMSC adhesion complex.…”
Section: Patterning Structuresmentioning
confidence: 97%
“…Alternatively, a self-assembled monolayer ͑SAM͒ substrate was developed to create arrays of spatially distinct hMSC culture environments. 147 A broad range of cell adhesion peptide densities of hMSCs adhered to patterned features was observed. Moreover, the peptide density significantly affects the formation, extension, and focusing the hMSC adhesion complex.…”
Section: Patterning Structuresmentioning
confidence: 97%
“…Many have employed this strategy to immobilize ECM-derived biomolecules for ultimate characterization of their effects on cell adhesion [103][104][105][106] . Popular immobilization strategies in the past have been based on adsorption or covalent modification of a protein's functional group(s) to a chemically activated surface [107][108] .…”
Section: Click Immobilization Of Peptides On 2d Surfacesmentioning
confidence: 99%
“…In turn, these aldehydes reacted with amine-terminated RGD to form patterned cell adhesive domains on the SAM. 68 We recently developed a localized SAM replacement approach within microfluidic channels to pattern peptide immobilization 69 (Fig. 4).…”
Section: Biomaterials As Cell Culture Substratesmentioning
confidence: 99%
“…However, our group recently demonstrated that patterned cell adhesive domains that were formed via a microfluidic patterning approach within a bio-inert tri(ethylene glycol) background were stable for more than 14 days under standard culture conditions. 69 In addition, the prospect of SAMs as cell culture substrates has led to the emergence of numerous commercial sources for gold substrates that address issues related to substrate quality control, as well as numerous sources for alkanethiols that alleviate the limitations associated with chemical synthesis. SAM formation is also a relative simple and robust process: gold substrates can be immersed in aqueous or ethanolic solutions of alkanethiols for a few hours to a few days, resulting in the formation of reproducible, well-packed monolayers.…”
Section: Sam Limitations and Practicalitiesmentioning
confidence: 99%